2007
DOI: 10.1063/1.2805216
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the bandwidth-length product: Graded index microstructured polymer optical fiber

Abstract: Large core multimode polymer fibers for high data rate transmission are an important growth area. The conventional approach to reducing the intermodal dispersion in such fibers is to use a graded index (GI) profile. More recently, microstructures rather than differences in chemical composition have been used to produce the GI structure. We compare the bandwidth performance of two GI microstructured fibers to a conventional GI fiber made from the same material. The microstructured fibers not only show excellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Since then mPOFs with a large variety of hole structures and thus specific optical properties, have been fabricated at the OFTC, including endlessly single-mode mPOFs [2][3], multi-mode graded-index mPOFs (GImPOFs) [2,4], hollow-core photonic bandgap guiding mPOFs [2][3]5], highly birefringent mPOFs [2], twin-core mPOFs, [2], rectangular core mPOFs [4], solution-doped mPOFs [3,6]. All these mPOFs have been made of conventional PMMA, which is commercially available in optical-grade quality granulates and low industry-grade solid rods.…”
Section: Introductionmentioning
confidence: 99%
“…Since then mPOFs with a large variety of hole structures and thus specific optical properties, have been fabricated at the OFTC, including endlessly single-mode mPOFs [2][3], multi-mode graded-index mPOFs (GImPOFs) [2,4], hollow-core photonic bandgap guiding mPOFs [2][3]5], highly birefringent mPOFs [2], twin-core mPOFs, [2], rectangular core mPOFs [4], solution-doped mPOFs [3,6]. All these mPOFs have been made of conventional PMMA, which is commercially available in optical-grade quality granulates and low industry-grade solid rods.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first fabrication of microstructured Polymer Optical Fibers (mPOFs) in Polymethyl methacrylate (PMMA, n=1.49 @589.3nm, 20°C) by Eijkelenborg et al [13], mPOFs have been made using a variety of polymers, such as Topas (cyclic olefin copolymer) [15][16][17] and biodegradable polymers [18]. The standard single-mode mPOF has a triangular hole structure with a single hole size, but much more complicated hole structures can be made, such as the one used to make for example graded-index mPOFs [19,20]. Argyros et al fabricated the first hollow-core bandgap mPOF with PMMA [21] and Cox el al.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on similar fibres [2] have shown that the bandwidth-length product is not constant with fiber length. We expect that Modal filtering is playing a significant role in the generation of this high bandwidth.…”
Section: Resultsmentioning
confidence: 97%
“…Typically these data links operate in the visible spectrum and the data rates of these links are low and limited by the bandwidth of the POFs. In previous works it has been demonstrated that utilising microstructure -microstructured polymer optical fibres (mPOF) [1] -significant improvements in the bandwidths can be achieved [2,3].…”
Section: Introductionmentioning
confidence: 99%